O uso de formas do subjuntivo frente a outras formas verbais na expressão de opinião, condição e finalidade na fala de Salvador - Joana Angelica Santos Lima (2018)
This research analyzes the use of forms of subjunctive versus other verbal forms (indicative and infinitive) in substantive clauses that express opinion (as a complement to the main clauses with the verbs acreditar and crer), in adverbial clauses that express the condition initiated by the conjunction se and in adverbial clauses that express purpose initiated by the conjunction para (que) in the speech of women of Salvador (BA). The approach is based on the theories of Labovian variationist sociolinguistics, sociofunctionalism and literacy. The qualitative and quantitative analysis was based on corpus data consisting of speech collected in 27 interviews with female informants in the city of Salvador. A questionnaire and a reading and writing test were also applied to evaluate the informants' literacy levels. Three hypotheses were tested: (a) there is variation in the use of subjunctive forms versus other verbal forms (indicative and infinitive) in the considered substantive, conditional and final clauses; (b) the variation in the use of subjunctive forms versus other verbal forms (indicative and infinitive) in the considered substantive, conditional and final clauses is controlled by intralinguistic variables; and (c) the variation in the use of subjunctive forms versus other verbal forms (indicative and infinitive) in the considered substantive, conditional and final clauses is controlled by extralinguistic variables. The results of the analysis of the corpus allowed to verify that the first hypothesis, considered strictly as it was elaborated, does not proceed, since there is no variation in the considered substantive, conditional and final clauses: (i) in the considered substantive clauses, the use of the forms of subjunctive is determined by the verb tense of the main and subordinate clauses as well as by the expression of a greater degree of doubt; (ii) in the considered conditional clauses, the use of the forms of subjunctive is determined by the verb tense of the subordinate clause as well as by the expression of counterfactuality or eventuality; and (iii) in the considered final clauses, the use of the forms of subjunctive is determined by the presence of conjunctive locution para que. The analysis of the final clauses was reframed in terms of type of clauses (clause with forms of subjunctive and clause with forms of infinitive), and the actual existence of variation was verified. Considering the reframing of the analysis of the final clauses, the second and third hypothesis proceed, since the intralinguistic variable explicitness of the subject of subordinate clause (explicit subject favors final clauses with forms of subjunctive) and the extralinguistic variable level of literacy (medium and high levels of literacy favor final clauses with forms of subjunctive).